Scalable Manufacturing of MXene Films: Moving toward Industrialization - Yu, Minghao; Feng, Xinliang (Matter, 2020)
Industry-scale manufacturing techniques hold the key to the ultimate commercialization of MXene products. In Matter, Taylor, Gogotsi, and colleagues demonstrate a drop-casting method to prepare scalable and micro-patternable MXene films on hydrophobic substrates, highlighting the excellent potential for the commercial application in electromagnetic interference shielding.
CRIS-Team Scopus Importer:2023-03-20